Intercity Impacts of Work-from-Home with Both Remote and Non-Remote Workers - Jan K. Brueckner; S. Sayantani (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper summarizes the results from generalizing the simple two-city WFH model of Brueck-ner, Kahn and Lin (2021) through the addition of a group of non-remote workers, who must live in the city where they work. The results show that the main qualitative conclusions of BKL regarding the intercity effects of WFH are unaffected by this modification, with WFH yielding the same aggregate population and employment changes in the two cities and the same house-price and wage effects as in the simpler model. This conclusion is useful because it establishes the robustness of BKL's highly parsimonious model.
Keywords: R12; R23; 330; work-from-home; remote work; amenities; productivity